2008
DOI: 10.1080/09578810802060785
|View full text |Cite
|
Sign up to set email alerts
|

What drives productivity in Tanzanian manufacturing firms: technology or business environment?

Abstract: Using cross-sectional firm-level data, this paper examines the determinants of productivity among manufacturing firms in Tanzania. In particular, it seeks to evaluate the relative importance of technological advances and the business environment in which firms operate in affecting productivity. Of the technological variables, R&D as well as product and process innovation, licensing of technology, and training of employees fail to have any impact; only foreign ownership, ISO certification and higher education o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 49 publications
3
58
1
Order By: Relevance
“…Our results show a more relevant role of innovation on firms' growth than the recent findings from the work of Goedhuys et al (2008Goedhuys et al ( , 2014, who found that supportive business environments have a greater influence on firms' performance than innovation activities. We also estimated different specifications in which we consider only technological innovations (products and process innovations) and the results are consistent with our main model (Appendix I).…”
Section: Informality Innovation and Growthcontrasting
confidence: 51%
See 2 more Smart Citations
“…Our results show a more relevant role of innovation on firms' growth than the recent findings from the work of Goedhuys et al (2008Goedhuys et al ( , 2014, who found that supportive business environments have a greater influence on firms' performance than innovation activities. We also estimated different specifications in which we consider only technological innovations (products and process innovations) and the results are consistent with our main model (Appendix I).…”
Section: Informality Innovation and Growthcontrasting
confidence: 51%
“…However, recent 7 studies on the role of innovation on firms' productivity found a much weaker impact. Goedhuys et al (2008Goedhuys et al ( , 2014 focused on the importance of various sources of technological knowledge on firm's productivity in developing countries. In Tanzania, they found that firm productivity is not enhanced by R&D, either product or process innovation, but business environment seems to play a more relevant role.…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a cross-sectional study of 275 firms in Tanzania, Goedhuys et al (2008) found a weak association between technological capabilities (proxied as R&D and other innovation activities) and labour productivity. Drawing on observations of 15 firms over 15 years in the worldwide integrated circuit manufacturing industry, Bapuji et al (2011) found that external knowledge acquisition and innovative activities (measured as patent citations) did not always lead to positive firm performance (measured as sales).…”
Section: Study Background and Research Questionmentioning
confidence: 99%
“…In addition, firms with greater foreign equity tend to be more efficient in terms of human resource management, and are more productive and more innovative than firms that are domestically-owned (Hallward-Driemeier et al 2006;Aydin et al 2007;Goedhuys et al 2008).…”
Section: Empirical Methodsmentioning
confidence: 99%